Forward-looking measures of higher-order dependencies with an application to portfolio selection - Felix Brinkmann; Alexander Kempf; Olaf Korn (University of Cologne, Centre for Financial Research (CFR), 2014)
This paper provides implied measures of higher-order dependencies between assets. The measures exploit only forward-looking information from the options market and can be used to construct an implied estimator of the covariance, co-skewness, and co-kurtosis matrices of asset returns. We implement the estimator using a sample of US stocks. We show that the higher-order dependencies vary heavily over time and identify which driving them. Furthermore, we run a portfolio selection exercise and show that investors can benefit from the better out-of-sample performance of our estimator compared to various historical benchmark estimators. The benefit is up to seven percent per year.
Keywords: G11; G13; G17; 330; option-implied information; dependence measures; higher moments; portfolio selection